Y=10 is the answer
I hope that helps
The actual answer would be $16.5625 but you can just say $16.5
Answer:
a= 2 b=-1
Step-by-step explanation:
a-3b=5
or, a= 5+3b_(i)
substituting value of a in 2a+b=3,
2×(5+3b)+b=3
or, 10+6b+b=3
or, 7b=3-10
or, 7b=-7
b= -1
substituting value of b in(i),
a=5+3b
=5+3×(-1)
=5-3
=2
12 ÷ 3 - 5(12) + 4(12 - 2)
= 4 - 60 + 4(10)
= -56 +40
= -16
Answer:
The graph is shifted 1 unit right
The graph is shifted 2 units down
Step-by-step explanation:
We are given
Parent function as
![f(x)=2^{x+3}-3](https://tex.z-dn.net/?f=f%28x%29%3D2%5E%7Bx%2B3%7D-3)
New function as
![g(x)=2^{x+2}-1](https://tex.z-dn.net/?f=g%28x%29%3D2%5E%7Bx%2B2%7D-1)
we can also write as
![g(x)=2^{x+3-1}-3+2](https://tex.z-dn.net/?f=g%28x%29%3D2%5E%7Bx%2B3%3Cstrong%3E-1%3C%2Fstrong%3E%7D-3%3Cstrong%3E%2B2%3C%2Fstrong%3E)
We can see that
1 is subtracted to x-value
and 2 is added to y-value
So, f(x) is shifted right by 1 unit
and
f(x) is shifted up by 2 unit